Aldosterone synthase inhibitors for cardiovascular diseases: A comprehensive review of preclinical, clinical and in silico data. (January 2021) - Lenzini, Livia; Zanotti, Giuseppe; Bonchio, Marcella; Rossi, Gian Paolo
Graphical abstract: Abstract: Aldosterone, the main mineralocorticoid hormone, plays a fundamental role in maintaining blood pressure (BP)and volume under hypovolemic conditions. However, in numerous diseases, where it is produced in excess, it plays a detrimental role and contributes to cardiovascular events and ultimately to death in a multitude of patients. The seminal observation that the fungicide-derivative fadrozole blunted steroidogenesis has led to develop several agents to inhibit aldosterone synthase (AS, CYP11B2), the mitochondrial NADH-dependent enzyme that is necessary for aldosterone biosynthesis. Aldosterone synthase inhibitors (ASI) have, thereafter, been conceived and investigated in phase I and phase II studies. We herein reviewed the ASIs available so far considering their chemical structure, the related aldosterone synthase binding and pharmacodynamic properties. We also examined the promising results obtained with ASIs that have already been tested in phase II human studies.